ANALISIS PROGRAM PENGUATAN PROFIL PELAJAR PANCASILA (P5) MELALUI OUTDOOR LEARNING DI SEKOLAH DASAR NEGERI KERET KREMBUNG - Sari, Rahmanda Novira; Indra Kurniawan , Machful (Jurnal Pendidikan Dasar Flobamorata, 2024)
This study aims to analyze and describe the development of strengthening the Pancasila profile through outdoor learning activities to shape the behavior or character of students at SDN Keret Krembung. Data collection techniques are interviews, observations, documentation and literature studies. The data analysis technique uses Miles and Huberman which consists of four components, namely data collection, data reduction, data presentation and drawing conclusions. The location in this research was conducted at the Keret Krembung State Elementary School. The results of this study found that optimizing the implementation of outdoor learning activities teaches students about the importance of the concept of caring for the environment and practicing it in real life at school. The Pancasila student profile strengthening program has been implemented and received good feedback from students. Because they are taught ways to appreciate local culture, tolerance, be independent and also have high creativity. In its application, there are several things that can become obstacles in this program, such as some students who have a less fast understanding.